FREQUENCY OF THE SYMPTOM OF EXCESSIVE DAYTIME SLEEPNESS IN COPD PATIENTS ASSOCIATED WITH OBSTRUCTIVE SLEEP APNEA-HYPOPNEA SYNDROME - Shakhboskhon Makhmudovich Akhmedov; Feruzakhon Shakhboskhonovna Akhmedova (Scholar Express Journals, 2023)
The high probability of a clinical diagnosis of OSAHS among COPD patients with excessive daytime sleepiness is determined by 4 or more specific signs and is 57.6%. It was noted that with the severity of the symptom of excessive daytime sleepiness, the likelihood of a clinical diagnosis of OSAHS increases (41.2% to 64.2%). A significant and severe degree of the symptom of excessive daytime sleepiness can be regarded as markers of a high probability of having OSAHS
Keywords: chronic obstructive pulmonary disease; obstructive sleep apnea-hypopnea syndrome; daytime sleepiness